ORIGINEA NATURII UMANE – FUNDAMENT AL DREPTURILOR OMULUI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human nature’s origin – the foundation of human rights.The contemporary evolutionary anthropology is forced to recognize that it still has many unsolved problems and fewer and fewer chances to explain the appearance of man, because it betrays its unscientific character. Only Christian anthropology, based on Holy Scripture and Holy Tradition, reveals that man is not a simple or random accident of existential chaos. „Only on the basis of the revealed teaching, humanity finds its true ontological nature, which illuminates its origins and perspectives of existence.” Man is not the descendant of some animal ancestors, as he was created in a special and unique manner in all aspects. The Holy Fathers observe within man the purpose of creation, „a vast being, a huge ladder on which all possible themes ascend and descend between earth and heaven.”